2005
DOI: 10.1108/02641610510618036
|View full text |Cite
|
Sign up to set email alerts
|

Online journals: their impact on document delivery

Abstract: Purpose -To examine some of the ways in which electronic resources have made an impact on traditional interlending practices and how some userpractices have begun to change. Design/methodology/approach -This study uses both quantitative and qualitative data. The qualitative data were gathered through a questionnaire about the impact of electronic resources and the use of ILL. Comparisons of change were made with document suppliers. Findings -The electronic full-text is as yet unable to fully meet the needs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…One article explored the changing function of interlibrary loan departments (Robertson, 2003). Online journals have also influenced the use of print journals (De Groote & Dorsch, 2001) and document delivery (Echeverria & Barredo, 2005). The literature reviewed offered few studies dealing strictly with medical students' interlibrary loan usage.…”
Section: Literature Reviewmentioning
confidence: 98%
“…One article explored the changing function of interlibrary loan departments (Robertson, 2003). Online journals have also influenced the use of print journals (De Groote & Dorsch, 2001) and document delivery (Echeverria & Barredo, 2005). The literature reviewed offered few studies dealing strictly with medical students' interlibrary loan usage.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Research from Spain, (Echeverria and Barredo, 2005) (Gillet, 2008), and concluded that, "In general, the use of document delivery in university libraries has decreased since the introduction of a critical mass of online journals from 2000 onwards." Research from Illinois reported a decline of nearly 26% from 1999 to 2003 in the number of ILL requests, (Wiley and Chrzastowski, 2005).…”
Section: Later Russon Concludes That "Ill Is Not Used As An Alternmentioning
confidence: 99%
“…Figures 4a-4e represent the date distribution of requests in another way: requests are grouped in time-ranges, (as in Echeverria and Barredo, 2005), in order to highlight possible trends in requests for recently published and older articles. Pie charts in figures 4a'', 4b'', 4c'', 4d'', 4e'', provide further insight into the publication date distribution of requests within the last three years, showing that current publications are increasingly involved in document supply.…”
Section: Insert Figure 3 Herementioning
confidence: 99%
“…Ce phénomène, outre le fait qu'il entraîne la reconnaissance d'une certaine notoriété tant pour les revues citées que pour les chercheurs eux-mêmes, constitue une méthode de recherche bibliographique à part entière qui est à l'origine de la consultation d'articles électroniques et de commandes de photocopies d'articles d'une façon plus traditionnelle. [4][5][6] Dans ce contexte très évolutif, nous avons voulu étudier la relation entre les citations des revues du domaine pharmacologique et pharmaceutique comme Thérapie et les commandes des articles publiés dans ces revues auprès de l'INIST-CNRS (Institut National de l'Information Scientifique et Technique), plus grand fournisseur de documents scientifiques en France. Notre étude a donc pour objectif de confirmer l'hypothèse selon laquelle les commandes d'articles papier reflètent de moins en moins la réalité des activités de recherche dans notre discipline et donc n'est plus un indice pour la citation des revues.…”
Section: Introductionunclassified